Characterizing discourse group roles in inquiry-based university science labs - Tong Wan; Juliette Pimbert; Reshawna L. Chapple; Ying Cao; Pierre-Philippe A. Ouimet (Physical Review Physics Education Research, 2025)
Group work is commonly adopted in university science laboratories. However, student small-group discourse in university science labs is rarely investigated. We aim to bridge the gap in the literature by characterizing student discourse group roles in inquiry-based science labs. The instructional context for this study was a summer program hosted at a private research university in the eastern United States. The program was designed as a bridge program for matriculating students who were first generation and/or deaf or hard of hearing (DHH). Accommodations such as interpreters and technological tools were provided for DHH students. We analyzed 19 students’ discourse moves in five lab activities from the video recordings, resulting in a total of 48 student-lab units. We developed codes to describe student discourse moves: asking a question, proposing an idea, participating in discussion, chatting off-task, and talking with instructor. Through a cluster analysis using the 48 student-lab units on quantified discourse moves, we identified four discourse styles, high on-task high social, high on-task low social, low on-task high social, and low on-task low social. The results show that individual students tended to demonstrate varying discourse styles in different lab activities; students’ discourse styles within the same groups tended to be aligned with their group members. By examining group members’ discourse styles in mixed-gender groups, we did not observe a difference in engagement levels between female and male students. DHH students in mixed hearing ability groups, however, were observed to have a lower level of engagement compared to their non-DHH group members. We discuss possible factors that may have contributed to the observations for genders and students with different hearing abilities. We also provide suggestions for promoting equitable small-group discourse in university science labs.